1966
DOI: 10.1042/bj1000373
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of streptococci by lactoperoxidase, thiocyanate and hydrogen peroxide. The effect of the inhibitory system on susceptible and resistant strains of group N streptococci

Abstract: 1. The growth of the lactoperoxidase-sensitive Streptococcus cremoris 972 in a synthetic medium was inhibited by lactoperoxidase and thiocyanate. The glycolysis and oxygen uptake of suspensions of Strep. cremoris 972 in glucose or lactose were also inhibited. The lactoperoxidase-resistant Strep. cremoris 803 was not inhibited under these conditions but was inhibited in the absence of a source of energy. 2. Lactoperoxidase (EC 1.11.1.7), thiocyanate and hydrogen peroxide completely inhibited the hexokinases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(62 citation statements)
references
References 10 publications
3
59
0
Order By: Relevance
“…Oram & Reiter (1966) and Mickelson (1966) suggested that the LP system, by oxidizing the thiol groups of a number of enzymes, interfered with glycolysis in some streptococci. More recently, Aune et al (1977) have examined the binding of the thiocyanate anion to bovine serum albumin in the presence of the LP system and have found that this involved the thiol groups of the protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oram & Reiter (1966) and Mickelson (1966) suggested that the LP system, by oxidizing the thiol groups of a number of enzymes, interfered with glycolysis in some streptococci. More recently, Aune et al (1977) have examined the binding of the thiocyanate anion to bovine serum albumin in the presence of the LP system and have found that this involved the thiol groups of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli NCTC 9703 and Streptococcus lactis NCDO 509 were used throughout. The effect of different quantities of OSCN-was examined on E. coli at 37 "C suspended in ammonium-salts glucose medium (Reiter et a/., 1976) and on S. lactis at 30°C suspended in the synthetic medium of Reiter & Oram (1962) from which cysteinelwas omitted. Both media were adjusted to pH 5.5 for better comparison with activity of the LP system (Reiter et a/., 1976).…”
Section: Introductionmentioning
confidence: 99%
“…These include immunocompetent T and B lymphocytes, polymorphonuclear leukocytes, macrophages (27)(28)(29), immunoglobulins, especially secretory IgA (29,30), and components of complement system (25,31,32). Additional soluble factors which are active against streptococci, staphylococci and tumor viruses (33)(34)(35) have also been identified. Of these components, the developmental characteristics of secretory IgA in the human colostrum and milk have been studied most extensively.…”
Section: Composition Of Human Milkmentioning
confidence: 99%
“…A stabilization period of two weeks preceded the 12-week experimental phase. More detailed information about the animals and the experimental design has been given in a previous paper (Tuori and Poutiainen 1977 Oram and Reiter (1966 a): 3 ml of phosphate buffer (0.1 M, pH 6.7), which contained 0.01 % o-dianisidine (Sigma Chemical Co., St. Louis, Mo. ), was pipetted into a glass cuvette (1 cm).…”
Section: Arrangement Of the Feeding Trialmentioning
confidence: 99%
“…The inhibitory system catalyzed by LP requires the presence of hydrogen peroxide and thiocyanate or some other oxidigable substance (halides) (Reiter et al 1964, Oram and Reiter 1966a, b, Klebanoff et al 1966). This system is nonspecifically bactericidal or bacteriostatic and it has been found to affect numerous gram-positive and gram-negative saprophytic and pathogenic bacteria (Reiter et al 1964, Klebanoff et al 1966, Mickelson 1966, Klebanoff 1967, Hamon and Klebanoff 1973, Hoogendoorn and Moore,r 1973, Reiter et al 1976).…”
Section: Introductionmentioning
confidence: 99%